2011
DOI: 10.2114/jpa2.30.161
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Season and Light Intensity on the Core Interthreshold Zone

Abstract: The hypothesis tested in the present study is a seasonal difference in the core interthreshold zone (CIZ), as we suggested in an earlier study that individual awareness of heat may change the CIZ due to thermoregulatory behavior. A series of human experiments were carried out in a climatic chamber in January and August of 2009 and January of 2010. The air temperature in the chamber was controlled at 20-24°C. Subjects wore a water-perfused suit that was perfused with 25°C water at a rate of 600 cc/min. They exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Because the lighting and season effect to the CIZ was confirmed in the previous study [3], illuminance was carefully controlled to be at 1000 lx, and all experiments were conducted from August to September as described in the experimental protocol of our previous study [4]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the lighting and season effect to the CIZ was confirmed in the previous study [3], illuminance was carefully controlled to be at 1000 lx, and all experiments were conducted from August to September as described in the experimental protocol of our previous study [4]. …”
Section: Methodsmentioning
confidence: 99%
“…Taking advantage of the pioneering work by Mekjavic et al [1], who proposed a methodology for determining the CIZ using a water bath, Kakitsuba et al [2] devised an alternative method using water-perfused suits, and have conducted a series of studies to investigate the CIZ. In one previous study [3], it was found that the CIZ was twofold wider in the summer than in the winter, and also found that the CIZ was a nearly twofold wider range at a luminance of 36 cd/m 2 compared with that observed at 18 cd/m 2 , indicating the possible incorporation of a non-visual pathway into the temperature regulation system. In another previous study [4], it was found that the peripheral interthreshold zone (PIZ) was proportionally correlated with the CIZ.…”
Section: Introductionmentioning
confidence: 96%
“…Because the effect of lighting and season on the CIZ was confirmed in a previous study 5 , luminance was carefully controlled at 1,000 lx, and all experiments were conducted from August to September, as described in the experimental protocol of our previous study 7 .…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Since both the T c and mean skin temperature contribute to the control of sweating and shivering, constant is required to be independent of thermal responses due to changes in Although three different experimental methods have been proposed to keep constant 1,2,3 , Kakitsuba et al 4 devised an alternative method using water-perfused suits, following the method proposed by Mekjavic et al 3 , and demonstrated a seasonal change in the CIZ, and light dependence of the CIZ, which indicated the possible incorporation of a non-visual pathway into the human thermoregulation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A constant mean skin temperature (normalTtrue¯sk) is required to be independent of thermal responses due to changes in normalTtrue¯sk, and is recognized as reliable information for evaluating the characteristics of body temperature regulation. Kakitsuba et al [6] demonstrated a seasonal difference in the CIZ as well as the effect of light intensity on the CIZ. The latter effect in particular indicates the possible incorporation of the non-visual pathway into the temperature regulation system.…”
Section: Introductionmentioning
confidence: 99%